Iodine supported poly(4-vinylpyridine): Efficient and recoverable catalyst for the synthesis of 3,3-diheteroaromatic oxindoles - Khaligh, Dr. Nader Ghaffari; Mutalabisin, Fathiy (Malaysian Catalysis-An International Journal, 2023)
An efficient methodology for the synthesis of 3,3-diheteroaromatic oxindole derivatives has been demonstrated by coupling indole-2,3-dione (isatin) with differently substituted indoles and pyrrole in the presence of iodine-supported on poly(4-vinylpyridine) under neutral and solvent-free conditions. The products were obtained in a short time and good to excellent yields.